Dekadensi Moral pada Remaja di Desa Raanan Baru - Silvestre Tristan Kawengian; Julien Biringan; Telly Delly Wua (CV. Kurnia Grup, 2026)
The phenomenon of moral decline among teenagers shows an increasingly worrying trend in the current era of development. This research aims to identify and examine the factors behind the occurrence of moral decadence in adolescents, as well as examine their impact on people's lives. This research uses a qualitative method with a case study approach to obtain an in-depth picture of the problem being studied. The findings of the study revealed that moral decline in adolescents is influenced by internal and external factors. These factors include the lack of optimal moral coaching and education, the influence of social media, and the condition of the social environment. The impacts include an increase in deviant behavior, a weakening of moral values in daily life, and a disruption of social relations in society. The data collection technique was carried out through direct observation and interviews with relevant informants. Based on the results of the research, it can be concluded that efforts to handle moral decadence in adolescents in Raanan Baru Village are carried out through various strategies, such as giving reprimands, coaching and moral education, delivering lectures, persuasive approaches, and providing advice on an ongoing basis.